Women in Islamic thought and philosophy in Baghdad and Andalusia for two centuries (5-6 AH/11-12 AD: comparative analytical study (Raparin Journal of Humanities (RJH), 2024)
Due to the extensive discourse and scholarly investigation pertaining to the status and involvement of women within the academic and cultural hubs of this particular area, the ongoing disparities and vehement confrontations between adherents and detractors of Islamic ideology regarding the standing and contributions of women persist. Consequently, it is imperative to approach this matter with a discerning outlook that is devoid of prejudiced perspectives and is situated within the framework of the historical epoch. Intellectuals, professionals in the field, and even members of the general public frequently engage in a wide range of discussions regarding women's rights and how their status among Muslims challenges this perception. Our study makes an academic and scientific effort to examine this problem from a Muslim point of view.During the period spanning the fifth and sixth centuries AH, which correspond to the eleventh and twelfth centuries AD, an examination of the historical contexts of Baghdad and Andalusia reveals significant developments. Through meticulous research and thorough analysis of various sources, it is essential to elucidate the perspectives held by Islamic groups and movements on the subject of women. It is imperative to gauge the extent to which societal cultures and traditions permeate religious attitudes towards women. Based on this foundation, a comparative analysis of the viewpoints espoused by Islamic religions and movements in both regions under scrutiny will be undertaken.The study presents the views of scholars and Philosophers in Baghdad and Andalusia, and explains the participation of women in public and cultural activities in both regions.